Numerical comparison of mathematical modeling approaches on the performances of link coupling beams - Musbar Musbar; Hanif Hanif; Khairul Miswar (International Journal of Advances in Applied Sciences, 2026)
The precision of inelastic steel-link response predictions in eccentrically braced frames (EBFs) is contingent on the material model employed. In the absence of comprehensive guidelines concerning constitutive choices for long-link coupling beams (LCBs), this study undertakes a comparative analysis of four models through nonlinear finite element simulations of three American Institute of Steel Construction (AISC) 341-22–compliant specimens under cyclic loading conditions in Ansys. Two mathematical formulations (Ramberg–Osgood and Kaufmann cyclic) and two plasticity-based formulations (multilinear kinematic hardening and isotropic hardening) were evaluated for shear strength, overstrength, and plastic rotation capacity. Mathematical models consistently generate stable hysteresis with uniform stiffness degradation, while plasticity-based models exhibit greater variability. It was observed that all specimens exceeded the nominal shear strength of 271.98 kN, attaining peak strengths of 350.72–391.86 kN (overstrength 1.29–1.44). The plastic rotations range from 0.039 to 0.051 rad, which exceeds the minimum requirement of 0.02 rad for long links. The Kaufmann cyclic model, when combined with multilinear kinematic hardening, has been shown to optimally reproduce key EBF hysteretic behavior. This advancement in model selection for numerical assessment and improvement in seismic performance predictions in performance-based design is a significant contribution to the field.